2013
DOI: 10.1093/jrr/rrs128
|View full text |Cite
|
Sign up to set email alerts
|

Nature of nontargeted radiation effects observed during fractionated irradiation-induced thymic lymphomagenesis in mice

Abstract: Changes in the thymic microenvironment lead to radiation-induced thymic lymphomagenesis, but the phenomena are not fully understood. Here we show that radiation-induced chromosomal instability and bystander effects occur in thymocytes and are involved in lymphomagenesis in C57BL/6 mice that have been irradiated four times with 1.8-Gy γ-rays. Reactive oxygen species (ROS) were generated in descendants of irradiated thymocytes during recovery from radiation-induced thymic atrophy. Concomitantly, descendants of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…Clonal expansion of cells with LOH at the Bcl11b locus has been reported as being one of the earliest detectable changes (along with Myc amplification) in the thymus post-irradiation but prior to the onset of lymphoma [ 37 ]. The presence of Notch1 Type 1 deletion-bearing cells in the normal mouse thymus [ 38 ] suggests that activating Notch1 deletions in the TL could result from selective expansion of cells with pre-existing spontaneous deletions, yet other evidence indicates that the recombination-mediated deletions are a later spontaneous event in the carcinogenic sequence [ 37 , 39 ], with no increase in deletion frequency in TL from irradiated compared to unirradiated mice [ 31 ]. Since studies of large panels of T-ALL have failed to find equivalent recombination-mediated deletions in the human NOTCH1 gene [ 32 ], this represents a mouse-specific tumour susceptibility that may contribute to their increased vulnerability to radiation-induced T cell tumours; though, the finding of a NOTCH1 Type 2 activating deletion (not recombination mediated) in a T-ALL patient [ 40 ] demonstrates that the mechanism has prima facie relevance to human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Clonal expansion of cells with LOH at the Bcl11b locus has been reported as being one of the earliest detectable changes (along with Myc amplification) in the thymus post-irradiation but prior to the onset of lymphoma [ 37 ]. The presence of Notch1 Type 1 deletion-bearing cells in the normal mouse thymus [ 38 ] suggests that activating Notch1 deletions in the TL could result from selective expansion of cells with pre-existing spontaneous deletions, yet other evidence indicates that the recombination-mediated deletions are a later spontaneous event in the carcinogenic sequence [ 37 , 39 ], with no increase in deletion frequency in TL from irradiated compared to unirradiated mice [ 31 ]. Since studies of large panels of T-ALL have failed to find equivalent recombination-mediated deletions in the human NOTCH1 gene [ 32 ], this represents a mouse-specific tumour susceptibility that may contribute to their increased vulnerability to radiation-induced T cell tumours; though, the finding of a NOTCH1 Type 2 activating deletion (not recombination mediated) in a T-ALL patient [ 40 ] demonstrates that the mechanism has prima facie relevance to human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that chromosomally aberrant cells were present in 25 of 26 (96%) of the thymic lymphomas examined, and the most frequent abnormality observed was trisomy or partial trisomy of chromosome 15 (16/26, 62%), which was consistent with earlier studies [ 45 , 46 , 47 , 48 , 49 ]. In addition, genomic alterations of the Ikaros / IKZF1 tumor suppressor gene and Notch1 oncogene were frequently observed in murine radiation-induced thymic lymphomas [ 50 , 51 , 52 , 53 , 54 ]. With the use of the distinct patterns of rearrangements at the T-cell receptor β (TCR-β) loci, Ohi et al found that clonal expansions were detected in a fraction of atrophic thymuses 30 days after irradiation [ 55 ].…”
Section: Genetic Alterations Of Murine Thymic Lymphoma Induced By Fx ...mentioning
confidence: 99%
“…In 2013, Tsuji et al published the results that examine the dynamic changes in the cell population that occurred within the thymuses of B6 female mice at various time points after FX treatment [ 52 ]. Their analysis included the course of the dynamic cytogenetic as well as genomic changes in the thymocyte populations, and clonal analysis of pre-lymphoma and established lymphoma cells using TCRβ gene rearrangements.…”
Section: Dynamic Changes In the Production Of Reactive Oxygen Species...mentioning
confidence: 99%